The Influence of Leadership and Emotional Intelligence on Employee Loyalty at PT Primanusa Sejati - Yanthi Meitry Gunawan; Khorida AR; Audrey Syahrani (Brilliant International Journal Of Management And Tourism, 2025)
This study examines the influence of leadership and emotional intelligence on employee loyalty in PT Primanusa Sejati, a distribution company that is facing improvement violation employee discipline that causes a decrease in sales levels. This study examines how leadership and emotional intelligence influence employee loyalty. A quantitative approach was used with a saturated sample of 39 employees. Primary data were collected through observation, interviews, and questionnaires, measured using a Likert scale, and processed using SPSS Version 22. The results indicate that all three variables significantly and positively influence employee loyalty. influence leadership and emotional intelligence on employee loyalty, with a combined explanatory power of 58.9%. This highlights the important role of leadership and emotional intelligence in supporting employee loyalty. This study contributes theoretically by providing stronger empirical evidence regarding the relationship between these variables in a corporate context, as well as serving as a practical reference for corporate management in developing human resource development strategies.